KARAKTERISTIK PENDERITA OMSK TIPE AMAN DENGAN RINITIS ALERGI DI IRJ RSUD DR. SOETOMO SURABAYA PERIODE JULI — DESEMBER 2017 - rifdah, salsabila nabilah; artono, artono; rahardjo, paulus (Universitas Tribhuwana Tunggadewi, 2021)
Chronic suppurative otitis media (CSOM) is a chronic inflammatory process of the middle ear mucosa and mastoid cavity accompanied by tympanic membrane perforation and a history of discharge from the ear canal for more than two months, whether continuous or intermittent. The presence of allergies is thought to play an important role in the occurrence of safe type CSOM. Until now there have been no studies on the characteristics of safe type CSOM patients with allergic rhinitis at the IRJ Hospital Dr. Soetomo Surabaya in 2017. Based on this, it is necessary to conduct research to find out information on the characteristics of patients with safe type CSOM with allergic rhinitis at the IRJ Hospital Dr. Soetomo Surabaya. This study was a retrospective descriptive observational study on secondary data in the form of medical records in patients with safe type CSOM with allergic rhinitis who were treated at the RSUD Dr. Soetomo Surabaya. The results showed that the highest sex distribution was women (75%), the most age group was the age range of 21-30 years (30.56%), the most regional origin was Surabaya (58.33%), the highest employment status was not working (50%), most patients had a history of allergies (86.11%), the most family history of allergic patients was eczema (41.67%), and most allergens were house dust mites (77.77%).